2002
DOI: 10.1148/radiol.2241011005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Low-Frequency Temporal Blood Oxygen Level–Dependent Fluctuations Indicate Reduced Functional Connectivity—Initial Results

Abstract: On the basis of the connectivity measure of low-frequency BOLD fluctuations, patients with MS exhibited lower functional connectivity between right- and left-hemisphere primary motor cortices when compared with that in control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(188 citation statements)
references
References 61 publications
7
177
2
2
Order By: Relevance
“…The identified brain regions are largely consistent with those in a previous study by our group, which aimed at discriminating between HC subjects and RRMS patients based on stationary FC (Richiardi et al, 2012); i.e., the left Heschl's gyrus, right rolandic operculum, and right superior parietal gyrus, were identified as being more strongly connected in HC subjects in both studies. Reduced stationary FC in MS patients is indeed commonly observed and is thought to stem from structural damage (Bonavita et al, 2011;Lowe et al, 2002;Richiardi et al, 2012;Roosendaal et al, 2010). However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 74%
See 1 more Smart Citation
“…The identified brain regions are largely consistent with those in a previous study by our group, which aimed at discriminating between HC subjects and RRMS patients based on stationary FC (Richiardi et al, 2012); i.e., the left Heschl's gyrus, right rolandic operculum, and right superior parietal gyrus, were identified as being more strongly connected in HC subjects in both studies. Reduced stationary FC in MS patients is indeed commonly observed and is thought to stem from structural damage (Bonavita et al, 2011;Lowe et al, 2002;Richiardi et al, 2012;Roosendaal et al, 2010). However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 74%
“…Alternative imaging methods, such as resting-state fMRI, have started to address the issue of hidden damage and shown disrupted stationary FC. While some studies restricted their analysis to the DMN or motor regions (Bonavita et al, 2011;Dogonowski et al, 2013;Lowe et al, 2002;Rocca et al, 2010), others have reported changes in several large-scale resting state networks, including the sensorimotor and executive control networks (Hawellek et al, 2011;Richiardi et al, 2012;Rocca et al, 2012;Roosendaal et al, 2010). Together, these results are very promising for characterizing the functional pathology of MS, but the relationship between structural damage and functional changes is still poorly understood (Schoonheim and Filippi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, timeseries correlation analysis has been utilized in studies of normal cognitive and emotional states (Greicius et al, 2003;Bartels and Zeki, 2005;Fox et al, 2005;Menon and Levitin, 2005), disease states (Lowe et al, 2002;Anand et al, 2005;Koshino et al, 2005;), and pharmacological interventions (Li et al, 2000;Honey et al, 2003;Peltier et al, 2005). Our study contributes to a rapidly growing body of knowledge regarding normal and abnormal functional neural circuitry.…”
Section: Discussionmentioning
confidence: 97%
“…Several specific approaches have been implemented (Horwitz, 2003), and their relative merits have not been established. The timeseries correlation method (Biswal et al, 1995;Lowe et al, 1998) examines interregional correlations within individual subjects over the timecourse of an experiment, and has been effectively applied to measure functional connectivity across a wide range of cognitive and physiological states (Li et al, 2000;Lowe et al, 2002;Greicius et al, 2003;Honey et al, 2003;Anand et al, 2005;Bartels and Zeki, 2005;Fox et al, 2005;Koshino et al, 2005;Menon and Levitin, 2005;Peltier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous low-frequency oscillations in regional cerebral blood flow and oxygenation in animals have been observed with laser Doppler flow, fluororeflectometry, fluorescence video microscopy, and polarographic measurement of brain tissue (Lowe et al, 2002). Biswal and colleagues demonstrated that very low-frequency (o0.08 Hz) temporal fluctuations in BOLD weighted echoplanar imaging data are phase locked between areas of plausible functional connectivity (Biswal et al, 1995b).…”
Section: Introductionmentioning
confidence: 99%